Understand a School Improvement Project Carry Out in Secondary School: A Case Study - Ali Ünal; Aysel Ateş (Anı Publishing, 2019)
The study aims to evaluate the teacher professional development project which took place in a secondary state school in İstanbul, its processes and results to be considered towards the opinions of the teachers who are attended all project activities. The research, is conducted and designed in holistic single case pattern and typical case sampling method is used. Research data is obtained from 10 teachers who work in this school during the 2017-2018 academic year and attended all activities of the project by focus group interview method. Descriptive analysis was used. As a result it was seen that the project has created a continuous learning environment, became a motivation source, offered autonomy and being answer to the search for a meaning of teachers, continuous professional development. The research has shed light that schools should accomplish the activities towards their needs for development